The Potential for Relational Expertise and Common Knowledge in ECEC-University Cooperation - Tuulikki Ukkonen-Mikkola; Susanna Isotalo; Elina Lehtinen; Pauliina Kielinen; Raija Raittila; Heini Rasanen; Otto Virkkula; Tiia Pappila; Piia Parviainen; Tarja Liinamaa (Nordisk Barnehageforskning)
This research focused on the potential for relational expertise and the creation of common knowledge in network cooperation between early childhood education and care (ECEC) centres and university in the context of the ECEC Development Network. It examined how ECEC teachers, university lecturers and master’s students identified their own and other professionals’ knowledge through positioning. Focus group interviews and discourse analysis were utilised to explore the positions produced by the participants. The subject positions and the positions produced by the other participants corresponded. Teachers were positioned as experts in ECEC who combined theory and practice in their work. University lecturers were perceived as experts in theoretical knowledge and members of the scientific community. Moreover, ECEC teachers and master’s students positioned university lecturers as influencers in society. Master’s students were positioned as observers, novices, and transmitters of new perspectives, although teachers did not identify them as novices. In conclusion, despite some divergence between subject positions and the positions produced by the other participants, there is potential for creating common knowledge relationally within the context of the ECEC Development Network.